Marketing and health care organizations - Gilligan, Colin; Lowe, Robin (Radcliffe Medical Press, 1995)
The need for a more conscious, focused and proactive approach to the management of health-care organizations has increased substantially. One consequence of this is that health-care managers are having to look at managerial approaches and techniques that previously were the province of the private sector. Prominent among those is the whole area of marketing. This work takes a broad approach to the marketing process, highlighting some of the challenges that health-care managers and medical professionals are having to face. Having done this, the authors move on to examine some of the characteristics of good and bad management practice. It is against this background that, in subsequent chapters, they turn their attention to the question of marketing and how it might best contribute to the management of organizations throughout the health sector. Each chapter includes questions and checklists offering scope for applying marketing principles to primary and secondary health-care organizations of all types, sizes and specialities.
Keywords: sociální lékařství; Social Medicine; management, organizace a řízení zdravotnictví; ZDRAVOTNÍ PÉČE - ORGANIZACE